Relationship Between Critical Power and Different Lactate Threshold Markers in Recreational Cyclists - Valenzuela, Pedro L.; Alejo, Lidia B.; Montalvo-Pérez, Almudena; Gil-Cabrera, Jaime; Talavera, Eduardo; Lucia, Alejandro; Barranco-Gil, David (Frontiers in Physiology, 2021)
Purpose: To analyze the relationship between critical power (CP) and different lactate threshold (LT2) markers in cyclists. Methods: Seventeen male recreational cyclists [33 ± 5 years, peak power output (PO) = 4.5 ± 0.7 W/kg] were included in the study. The PO associated with four different fixed (onset of blood lactate accumulation) and individualized (Dmaxexp, Dmaxpol, and LTΔ1) LT2 markers was determined during a maximal incremental cycling test, and CP was calculated from three trials of 1-, 5-, and 20-min duration. The relationship and agreement between each LT2 marker and CP were then analyzed. Results: Strong correlations (r = 0.81–0.98 for all markers) and trivial-to-small non-significant differences (Hedges’ g = 0.01–0.17, bias = 1–9 W, and p > 0.05) were found between all LT2 markers and CP with the exception of Dmaxexp, which showed the strongest correlation but was slightly higher than the CP (Hedges’ g = 0.43, bias = 20 W, and p < 0.001). Wide limits of agreement (LoA) were, however, found for all LT2 markers compared with CP (from ±22 W for Dmaxexp to ±52 W for Dmaxpol), and unclear to most likely practically meaningful differences (PO differences between markers >1%, albeit <5%) were found between markers attending to magnitude-based inferences. Conclusion: LT2 markers show a strong association and overall trivial-to-small differences with CP. Nevertheless, given the wide LoA and the likelihood of potentially meaningful differences between these endurance-related markers, caution should be employed when using them interchangeably.